Machining of wood five brazilian native species - Dias Júnior, Ananias Francisco; Carvalho, Alexandre Monteiro de; Santos, Pablo Vieira dos; Silva, Marcelly Alves da (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2014)
This study was to compare the behavior of five native Brazilian species: angelim (Andira anthelmia), a canela (Anila firmula), cedro (Cedrela fissilis), ipê amarelo (Tabebuia alba) e a muiracatiara (Astronium lecointein) through testing machining. It was made ten samples for each kind of dimensions following the U.S. ASTM D 1666-87. Still determined the apparent density of the wood (g.cm-3) based on the NBR 7190 in order to establish possible relations For machining tests, all species behave well with relation to the sanding and drilling for peg no significant differences between the grades obtained. However, the ipê submitted the worst result for the planing test and cedro due to its smaller apparent density obtained the worst result front of drilling tests. With respect to turning test, species of ipê and canela were rated as the best among the tested species. Overall, it was concluded that the species showed potentials of uses in furniture, frames and general finishing occasions.